PERKEMBANGAN PROSES PENGIRIMAN NASKAH (KARYA PENULIS) DI ERA DIGITALISASI : STUDI PADA GRAMEDIA DIGITAL PUBLISHING SYSTEM - Rohmaniyah, Rohmaniyah; Walian Dan, Riki (UPT Perpustakaan Universitas Bengkulu, 2024)
This article examines the development of manuscript submissionprocesses in the era of digitalization, particularly through the Gramedia DigitalPublishing System, using a descriptive qualitative research method. The studydescribes how digital technology has transformed the way publishing operates,facilitating authors in submitting their works more efficiently. The advantages ofthis system, such as ease of access, fast processes, and structured manuscriptmanagement, are discussed alongside evaluations of potential drawbacks, such aslimited internet access and increased competition among authors. Thus, this articlehighlights the importance of adapting to technology to support the creative processand distribution of works in the digital era.